2013
DOI: 10.1017/s0007114513002961
|View full text |Cite
|
Sign up to set email alerts
|

Salt, fruit and vegetable consumption and blood pressure development: a longitudinal investigation in healthy children

Abstract: Low salt intake and high fruit and vegetable intake (FVI) have been shown to reduce blood pressure (BP) in adults. Longitudinal data on the independent effect of both FVI and salt intake on BP in healthy normotensive children are not available yet. In the present study, we aimed to characterise the concomitant influence of salt intake and FVI on BP development throughout childhood and adolescence. We examined 435 healthy subjects, for whom at least three repeated measurements of BP had been taken and who had p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
42
2
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 46 publications
9
42
2
4
Order By: Relevance
“…Prospective studies have shown the effects of diet on lifetime BP (201). Consumption of >1 servings of dairy products/day and >2 servings of fruits and vegetables/day throughout adolescence has shown to lead to about a 35% lower risk of elevated BP (202).…”
Section: Blood Pressure Target In Diabetic and Renal Diseasementioning
confidence: 99%
“…Prospective studies have shown the effects of diet on lifetime BP (201). Consumption of >1 servings of dairy products/day and >2 servings of fruits and vegetables/day throughout adolescence has shown to lead to about a 35% lower risk of elevated BP (202).…”
Section: Blood Pressure Target In Diabetic and Renal Diseasementioning
confidence: 99%
“…For example, it is widely believed that dietary intake of F & V is inversely related with blood pressure, and may prevent the development of hypertension [34]. However, other studies did not show any significant association [35] [36].…”
mentioning
confidence: 99%
“…Initial signs of success may include modified behaviors that promote slowing of the rate of weight gain, stabilization of weight, stabilization of body mass index (BMI), and eventually decrease in BMI. These behavioral changes can also improve comorbidities associated with obesity, including high blood pressure (Shi, Krupp, & Remer, 2014). If families regularly attend and actively participate in appointments and implement recommended changes, they are more likely to experience positive outcomes.…”
Section: Treatment Of Pediatric Obesitymentioning
confidence: 99%